Experimental study on stress concentration of nickel-base superalloy at elevated temperatures with an in situ SEM system. (December 2016) - Li, Chuanwei; Xie, Huimin; Liu, Zhanwei; Wang, Shibin; Li, Linan
Highlights: Stress concentration phenomenon of nickel-base superalloy was investigated with an SEM in situ system at elevated temperatures. 3D deformation of the stress concentration area of a U-notch sample was measured. Dual frequency grid pattern that can be used at the temperature up to 650 °C was fabricated to realize the measurement at various scales. Abstract: The increasing research focus on micro- or nano-mechanics at high temperature poses new challenges for researchers to realize the deformation measurement by means of microscopic devices. SEM (Scanning Electron Microscope)-based optical methods are desirable approaches due to their full field, high magnification and high sensitivity. The SEM with an electron optical system is to some extent preferable for high temperature experiments compared with those traditional optical methods. In this study, a novel SEM-based measurement method aiming at the characterization of mechanical properties of high temperature alloys is proposed. By designing and employing a dual frequency grids pattern, the in-plane and out-of-plane deformation measurement of a specimen with U-shaped notch (U-notch) can be realized simultaneously at temperature up to 650 °C. The mechanical parameters of the tested specimen are determined and the stress concentration effect at elevated temperatures is analyzed. The Baratta-Neal stress concentration solution is adopted to be compared with the experimental results. The measurement accuracy is also discussed in detail.